Placement of Teflon Sponges in Microvascular Decompression Procedure for Treatment of Hemifacial Spasm - Nan-xiang, Xiong; Lv-an, Chen; Zhi-jun, Chen; Hong-yang, Zhao (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Background Hemifacial spasm (HFS) is generally treated by microvascular decompression (MVD). Inadequate separation of vessel and nerve or adhesive inflammation surrounding the nerve root may cause recurrence.Objective To explore a method to reduce the incidence of adhesions and to ensure sufficient separation of the offending vessel and nerve during MVD.Methods Fifty-one patients diagnosed with HFS were studied. During the MVD procedure, Teflon sponges were placed between the offending vessels and medulla oblongata to push compressing vessels away from the facial nerve without contacting the nerve.Results Our method of placement of the Teflon sponge effectively shifts the compressing artery and ensures that both the Teflon sponge and offending vessels do not contact the root exit zone. This method also ensures that the Teflon sponge is fixed in place.Conclusion The technique described for the treatment of HFS provides an effective, safe, and durable resolution to patient symptoms that minimizes surgical complications and may be useful in treating HFS.
Keywords: facial nerve; hemifacial spasm; Teflon; microvascular decompression